Independence Versus Community: Gendered Contradictions in Margaret Laurence's The Stone Angel and The Fire-Dwellers - Gault, Cinda (Atlantis, 2010)
Hagar and Stacey, two of Margaret Laurence's protagonists not usually considered together, share a host of gendered contradictions in their efforts to live full and balanced lives. They are victimized by their efforts to survive, strive for agency only to find themselves more contained, and meet their needs by contributing to their own oppression.